Visually textual - Baharuddin, Mohd Nasir; Abd. Manan, Mohd Shahrudin; Salehuddin, Adam; Abdul Shukor, Shureen Faris; Abu Bakar, Shamsul (Universiti Putra Malaysia Press, 2016)
This video projection questions the perceptual relationship between ‘word’ and ‘image’. It delves into the rupture of representation that demarcates the signifier of word as a morphological syntax and its signified concept for assembling meanings. Instead of celebrating word as a phonological form for speech and verbal rhetoric, the video projection renegotiates the ontological idea of image as a gestural mediality to stimulate brain and senses.